Genetic parameter and character association studies in Indian mustard (Brassica juncea L. Czern and Coss): Genetic parameter and character association studies in Indian mustard (Brassica juncea L. Czern and Coss) - MAHAK SINGH; RUPENDRA SINGH; JAGDISH PRASAD CHAURASIYA; KULDEEP YADAV (Journal of Oilseeds Research, 2020)
Character association studies were carried out with 28 genotypes of Indian mustard. Analysis of variance estimates of all the ten characters studied were highly significant. Coefficient of variation for GCV and PCV were found high for the traits no. of secondary branches/plant, days to 50% flowering, 1000-seed weight and seed yield/plant. The character days to 50% flowering showed higher heritability with high genetic advance. Correlation study revealed that seed yield/plant had significant and positive association with plant height (0.48G and 0.32P), main raceme length (0.60G and 0.39P), number of siliquae/plant (0.58G and 0.39P), number of primary branches/plant (0.89G and 0.36P), number of secondary branches/plant (0.45G and 0.32P), number of primary branches/plant and oil content (0.52 G and 0.37P) at genotypic and phenotypic levels.